The contestation of da’wa on Youtube: Comparative study of Syubbanul Muslimin and At-Taufiq Salawat Group - Diya Annisaul Fauziah; Bobby Rachman Santoso (Jurnal Ilmu Dakwah, 2021)
In the development of da'wa, it is necessary to use media that is following the interests of the community, technology also plays an important role in the development of da'wa. Youtube is widely known by the public and can provide videos according to the wishes of customers so that they can provide Salawat services in the development of da'wa. The purpose of this journal is to find out that YouTube is the right da'wa medium to be used for the community, Salawat is the most emphasized in the da'wa media because Salawat is an art that the majority of people are interested in. The method used in this study is qualitative with a critical analysis approach, data collection techniques in this study are observation and interviews. This research was conducted so that the public understands the contestation between Syubbanul Muslimin and At-Taufiq in the development of da'wa and the impact of competition in the development of da'wa on netizens. With this journal, there will be problems. Why is there a contestation between Syubbanul Muslimin and At-Taufiq in the development of da'wa? And what is the impact of Syubbanul Muslimin and At-Taufiq competition in the development of da'wa for netizens? The results of this journal research explain that the two Salawat have healthy competition in providing attractiveness to the community, as one of the efforts in developing da'wa. Some netizens revealed that the competition between the two groups had a positive impact in the world of da'wa through youtube, that youtube was able to provide freedom of access to its followers, one of which was as an effective da'wa media. ***Pengembangan dakwah perlu menggunakan media yang mengikuti kepentingan masyarakat, teknologi juga berperan penting dalam pengembangan dakwah. Youtube dikenal luas oleh masyarakat dan dapat memberikan video sesuai keinginan pelanggan sehingga dapat memberikan layanan Salawat dalam pengembangan dakwah. Tujuan dari jurnal ini adalah untuk mengetahui bahwa youtube merupakan media dakwah yang tepat untuk digunakan bagi masyarakat, Salawat paling ditekankan dalam media dakwah karena Salawat merupakan seni yang diminati oleh sebagian besar masyarakat. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan analisis kritis, teknik pengumpulan data dalam penelitian ini adalah observasi dan wawancara. Penelitian ini dilakukan agar masyarakat memahami kontestasi Syubbanul Muslimin dan At-Taufiq dalam pengembangan dakwah dan dampak persaingan dalam pengembangan dakwah pada netizen. Dengan jurnal ini, akan ada masalah. Mengapa ada kontestasi antara Syubbanul Muslimin dan At-Taufiq dalam pengembangan dakwah? Dan apa dampak kompetisi Syubbanul Muslimin dan At-Taufiq dalam pengembangan dakwah bagi netizen? Hasil penelitian jurnal ini menjelaskan bahwa kedua grup Salawat memiliki persaingan yang sehat dalam memberikan daya tarik kepada masyarakat, sebagai salah satu upaya dalam mengembangkan dakwah. Beberapa netizen mengungkapkan bahwa persaingan antara kedua kelompok tersebut berdampak positif dalam dunia dakwah melalui youtube, bahwa youtube mampu memberikan kebebasan akses kepada para pengikutnya, salah satunya sebagai media dakwah yang efektif.